Biochemical Characterization of Two Rhamnogalacturonan Lyases From Bacteroides ovatus ATCC 8483 With Preference for RG-I Substrates - Wang, Weiyang; Wang, Yibing; Yi, Haoting; Liu, Yang; Zhang, Guojing; Zhang, Le; Mayo, Kevin H.; Yuan, Ye; Zhou, Yifa (Frontiers in Microbiology, 2022)
Rhamnogalacturonan lyase (RGL) cleaves backbone α-1,4 glycosidic bonds between L-rhamnose and D-galacturonic acid residues in type I rhamnogalacturonan (RG-I) by β-elimination to generate RG oligosaccharides with various degrees of polymerization. Here, we cloned, expressed, purified and biochemically characterized two RGLs (Bo3128 and Bo4416) in the PL11 family from Bacteroides ovatus ATCC 8483. Bo3128 and Bo4416 displayed maximal activity at pH 9.5 and pH 6.5, respectively. Whereas the activity of Bo3128 could be increased 1.5 fold in the presence of 5 mM Ca2+, Bo4416 required divalent metal ions to show any enzymatic activity. Both of RGLs showed a substrate preference for RG-I compared to other pectin domains. Bo4416 and Bo3128 primarily yielded unsaturated RG oligosaccharides, with Bo3128 also producing them with short side chains, with yields of 32.4% and 62.4%, respectively. Characterization of both RGLs contribute to the preparation of rhamnogalacturonan oligosaccharides, as well as for the analysis of the fine structure of RG-I pectins.